Dialektika Islam Nusantara Di Ruang Digital : Pergulatan Narasi dan Otoritas Dalam Debat Gus Ajir Vs Herri Pras - Moh. Jazuli; Yusril Amin Faqih; Ilham Firmansyah (Indo Publishing, 2026)
The debate between KH. Ajir Ubaidillah (Gus Ajir) and Herri Pras in January 2026 represents a significant phenomenon in the study of Islam Nusantara in the digital age. This article examines the debate as a site of contestation between two religious approaches: the sanad-based scholarly tradition (Aswaja) and literal-scriptural criticism of traditional practices. Utilizing a digital discourse analysis approach, this study demonstrates that the debate on tabarruk, karamah, and khurafat is not merely a theological argument but rather a reflection of the fragmentation of religious authority in the digital public sphere. This article argues that the debate embodies a clash between the